Risk assessment of aflatoxin B1 in herbal medicines and plant food supplements marketed in Malaysia using margin of exposure and RISK21 approaches - Ab Dullah, Siti Soleha; Sabran, Mohd Redzwan; Hasiah, Ab Hamid; Abdullah, Rozaini (BioMed Central, 2023)
Aflatoxin B1 (AFB1) is a mycotoxin produced by several species of Aspergillus fungi which can cause liver cancer in animals and humans. This study aims to perform the risk assessment of AFB1 in herbal medicines and plant food supplements (PFS) in Malaysian market. A total of 31 herbal medicines and PFS were purchased through online platforms and over the counter using a targeted sampling strategy. Of 31 samples analysed using the ELISA method, 25 (80.6) were contaminated with AFB1 at levels ranged from 0.275 to 13.941 μg/kg. The Benchmark Dose Lower Confidence level of 10 (BMDL10) of 63.46 ng/kg bw/day and the estimated dietary intake of the adult population ranged from 0.006 to 10.456 ng/kg bw/day were used to calculate the Margin of Exposure (MOE). The MOEs for 24 (96) out of the 25 positive samples were lower than 10,000. The RISK21 matrix revealed that AFB1 exposure levels from herbal medicines and PFS differed greatly over the world. The calculated population risk of acquiring liver cancer from AFB1 exposure ranged from 0 to 0.261 cancers/100,000 populations/year and accounted for an estimated percentage of liver cancer incidence ranged from 0.002 to 4.149. This study revealed a moderate risk of liver cancer attributable to AFB1 from herbal medicine and PFS among Malaysian populations and emphasised an urgency for risk management actions.